Constructivist Biology Learning Experiences Profile of Senior High School Students in South Sulawesi - Suhardi Aldi; Adnan Adnan; Andi Asmawati Azis (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe the constructivist Biology learning experience of high school students in South Sulawesi. The research subjects consisted of 525 students from 7 districts/cities in South Sulawesi. The method used in this study was a descriptive survey using a closed questionnaire instrument and a Likert scale. The data collection technique used a Google Forms platform that contained a questionnaire. The data obtained were processed using descriptive and inferential analyses. The results showed that the constructivist biology learning experience of students in South Sulawesi included learning personality indicators of 64.20%, reflection thinking of 68.89%, problem solving and investigation relevance to daily life of 69.55%, collaborative learning of 71.00%, discussion of 72.75%, teaching scaffolding of 68.29%. Then a very low correlation coefficient value is shown in the learning personality indicator with problem solving investigation of 0.15. The strong correlation coefficient value on the collaborative learning indicator with discussion is 0.60. The findings of this study indicate that the overall constructivist learning experience of students in South Sulawesi is still moderately low and the correlation coefficient between the dominant indicators is still weak. Therefore, efforts are needed to improve the constructivist Biology learning experience to optimize learning effectiveness.